2020
DOI: 10.3390/biomedicines8100398
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of Non-Polarized Lung Macrophages with Poor Phagocytic Function in Chronic Obstructive Pulmonary Disease (COPD)

Abstract: Lung macrophages are the key immune effector cells in the pathogenesis of Chronic Obstructive Pulmonary Disease (COPD). Several studies have shown an increase in their numbers in bronchoalveolar lavage fluid (BAL) of subjects with COPD compared to controls, suggesting a pathogenic role in disease initiation and progression. Although reduced lung macrophage phagocytic ability has been previously shown in COPD, the relationship between lung macrophages’ phenotypic characteristics and functional properties in COP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…EGFR, a member of the “ErbB signaling pathway”, has also been found to mediate macrophage activation in the pathological context [ 50 , 51 ]. Macrophages are key immune effector cells in the pathogenesis of COPD, and BAL-macrophages from COPD patients have been reported to present a non-polarized phenotype that confers them a poor immune response [ 52 , 53 ]. As the “ErbB signaling pathway” was also detected in our in silico analysis, the three miRNAs candidates might be implicated in the alteration of the EGFR role in macrophage function in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR, a member of the “ErbB signaling pathway”, has also been found to mediate macrophage activation in the pathological context [ 50 , 51 ]. Macrophages are key immune effector cells in the pathogenesis of COPD, and BAL-macrophages from COPD patients have been reported to present a non-polarized phenotype that confers them a poor immune response [ 52 , 53 ]. As the “ErbB signaling pathway” was also detected in our in silico analysis, the three miRNAs candidates might be implicated in the alteration of the EGFR role in macrophage function in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Berenson and co-workers showed that macrophages from patients with COPD have impaired phagocytosis of respiratory pathogens which strongly correlated with COPD severity (FEV1% predicted) [63]. Studies from our laboratory recently showed that the majority of airspace macrophages in COPD do not express either M1 or M2 markers and that these "non-polarized" macrophages have significantly reduced phagocytic capacity compared to polarized (M1 or M2) macrophages [30]. In this study, airspace macrophages could be divided into 4 distinct groups using surface markers, as either M1, M2, dual positive for M1 & M2 (double polarized) or negative for both M1 & M2 markers (non-polarized).…”
Section: Macrophages and Copdmentioning
confidence: 95%
“…This switch in polarization is dynamic and induced predominantly by their microenvironment. The distinct M1 and M2 subtypes is an overly simplification of macrophage polarization, for example, 5% of the macrophages in lung cancer specimens express both M1 and M2 markers [29], and mixed macrophage polarization have been described in other lung conditions [29,30]. With the advent of genetic analysis and specifically single cell RNA sequencing technology, the basic macrophage characterization of M1 and M2 phenotypes has been challenged and may change in the near future [31].…”
Section: Macrophages Are Polarized To An M1 (Or T-helper Type 1 Cell ...mentioning
confidence: 99%
“…Among these cell types, alveolar macrophages provide the first line of defense against extrinsic organisms that reach the alveolar airspace, where distinct macrophage subpopulations exhibit distinct functional properties [14]. Macrophages have been characterized either as "classically" activated or M1 macrophages or "alternatively" activated or M2 macrophages [14,15]; however, macrophages negative for both M1 and M2 markers (non-polarized macrophages) are also reportedly associated with chronic inflammation [16,17]. A higher rate of non-polarized macrophages may account for impaired phagocytic activity and is associated with disease severity and progression in patients with chronic obstructive pulmonary disease (COPD) [16].…”
Section: Introductionmentioning
confidence: 99%